Case report: Identification of a novel TOR1AIP2::ETV6 transcript with FLT3-ITD mutation in acute myeloid leukemia progressed from myelodysplastic syndrome - Xia, Jun; Yang, Guanqun; Yu, Qingling; Zhang, Ruiyi; Li, Ge; Wang, Man; Sun, Hongli; Chen, Heng; Wang, Lingling; Chen, Ping; Gu, Kai-Li; Sun, Chao (Frontiers in Oncology, 2024)
Acute myeloid leukemia (AML), which is most common in adults, is a challenging hematological malignancy. The occurrence and the progression of AML are often accompanied by various gene fusions and/or mutations. Herein, we report the first case of a TOR1AIP2::ETV6 fusion transcript with a translocation of t(1;12)(q25;p13) in AML progressed from myelodysplastic syndrome (MDS) combined with an FLT3-ITD (internal tandem duplication) mutation. Further studies should focus on the biological functions of these novel chimeric products in disease onset and progression, as well as their potential as monitoring markers in disease regression.